LRFD specifications for structural supports for highway signs, luminaires, and traffic signals. (American Association of State Highway and Transportation Officials, 2015)
The 1st Edition of this book incorporates and builds upon the design specifications found in the Sixth Edition of Standard Specifications for Structural Supports for Highway Signs, Luminaires, and Traffic Signals, which it supersedes. The specification includes current research on LRFD calibration, loads, and resistances plus relevant specifications from other AASHTO documents. Completely new sections on Fabrication, Construction, Inspection, and Asset Management based upon best practices have also been added.